Microbial hotspots in a relict fog-dependent Tillandsia landbeckii dune from the coastal Atacama Desert - Jaeschke, Andrea; May, Simon Matthias; Hakobyan, Anna; Mörchen, Ramona; Bubenzer, Olaf; Bernasconi, Stefano Michele; Schefuß, Enno; Hoffmeister, Dirk; Latorre, Claudio; Gwozdz, Martina; Rethemeyer, Janet; Knief, Claudia (Global and planetary change, 2024)
The hyperarid Atacama Desert in northern Chile is considered to be one of the most hostile habitats for microbial life. Despite the extreme environmental conditions, isolated patches of vegetation exist in an otherwise barren landscape. Unique dune ecosystems dominated by rootless Tillandsia landbeckii vegetation occur at elevations of about 900-1200m asl within the coastal mountain range and receive water and nutrients mostly from the Pacific Ocean via fog deposition. The largest dunes can form over thousands of years, and may host diverse and abundant populations of microorganisms, sustained by fog moisture and nutrients via plant litter deposition. Relict dune ecosystems, with no living plants, are also common on this landscape. We investigated the microbial community structure in such a relict and stratified Tillandsia dune, located north of the Rio Loa canyon, to explore links between plant occurrence and past hydroclimatic variations using a multi-proxy approach. Our results indicated multiple phases of dune growth with alternating plant colonization, dieback, and sand accumulation during the past ∼1300years. Hydrogen isotope analysis of fossil leaf wax n-alkanes showed a distinct pattern of more humid conditions during the Medieval Climate Anomaly and increasing aridity during the Little Ice Age. We found that microbial abundance and diversity were generally higher in and just beneath core sections with elevated amounts of plant material. Recurrent rewetting events during specific climatic periods in the past may have supported active microbial communities in the sand dune, sustained by plant resources. This is further supported by significant changes in foliar and sedimentary δ15N values. Most negative δ15N values concurred with higher n-alkane abundances and distinct shifts in microbial community structure, pointing to increased biological nitrogen cycling in the central part of the dune, where niche occupation occurred by nitrifying Thaumarchaeota. In contrast, the upper part of the dune core was characterized by low microbial diversity and abundance. The community was dominated by members of the Bacilli, which may have dispersed via dust during a generally more arid climate. The sand dune thus retains a unique and well-preserved environmental record that reflects concomitant changes in past hydrological (i.e., fog) conditions, plant growth and microbial abundance and diversity during late Holocene climate extremes.
Gesehen am 25.09.2024